Gay fathers' motivations for and feelings about surrogacy as a path to parenthood. Issue 4 (23rd February 2017) - Blake, L.; Carone, N.; Raffanello, E.; Slutsky, Jenna; Ehrhardt, A. A.; Golombok, S.
Abstract: STUDY QUESTION: Why do gay men choose to start their families through surrogacy? SUMMARY ANSWER: Most fathers chose surrogacy because they considered adoption to be a less desirable and/or accessible path to parenthood. WHAT IS KNOWN ALREADY: Little is known of gay fathers' motivations to use surrogacy as a path to parenthood over and above other forms of family building, such as adoption, and no studies have examined fathers' satisfaction with the surrogacy process. STUDY DESIGN, SIZE, DURATION: This study used a cross-sectional design as part of a larger investigation of parent–child relationships and child adjustment in 40 gay father surrogacy families. Multiple strategies (e.g. surrogacy agencies, social events and snowballing) were used to recruit as diverse a sample as possible. Data were obtained from 74 fathers (in 6 families only 1 father was available for interview). PARTICIPANTS/MATERIALS, SETTING, METHOD: Semi-structured interviews, lasting ~1 h, were conducted in the family home (65%) or over Skype (35%) with 74 gay fathers (35 genetic fathers, 32 non-genetic fathers and 7 fathers who did not know or did not disclose who the genetic father was), when the children were 3–9 years old. MAIN RESULTS AND THE ROLE OF CHANCE: Genetic and non-genetic fathers were just as likely to want to become parents and had similar motivations for choosing surrogacy as a path to parenthood. Most fathers ( N = 55, 74%) were satisfied with surrogacy and were satisfied ( N = 31. 42%) or had neutral feelings ( N = 21, 28%) about their choice of who would be the genetic father. Most fathers received supportive reactions to their decision to use surrogacy from both families of origin (e.g. parents, siblings) ( N = 47, 64%) and from friends ( N = 63, 85%). LIMITATIONS, REASONS FOR CAUTION: Although diverse recruitment strategies were used, data were obtained from a volunteer sample. Therefore, the possibility that fathers who had a positive surrogacy experience may have been more likely to participate in the study, and therefore introduce bias, cannot be ruled out. Due to the high average annual income of the fathers in the study, findings may not generalize to gay fathers with lower incomes. WIDER IMPLICATIONS OF THE FINDINGS: It is often assumed that parents' primary motivation for using ART is to have a genetic connection to the child. This study revealed that whilst genetic fatherhood was important for some gay fathers in surrogacy families, it was not important for all. This information will be of use to surrogacy agencies and organizations supporting men who are considering the different routes to parenthood. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by the Wellcome Trust [097857/Z/11/Z] and the Jacob's Foundation. None of the authors has any conflict of interest to declare. TRIAL REGISTRATION NUMBER: N/A.